(untitled) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2022)
The research aimed to evaluate biological alternatives for the management of root born fungal diseases and cleaner strawberry production in the municipality of Pamplona, Norte de Santander. An experiment in randomized block was carried out with seven treatments and four replicates at the San Francisco farm in the Vereda Monteadentro where the biopreparations were evaluated: MM, M6, Caldo Rizósfera and the Trichoderma fungi together with the chemicals Benomyl® and Ceraquint®. Twenty plants taken at random from the four central rows of each plot per treatment were evaluated, the variables incidence and area under the disease progress curve (ABCPE) were determined. The root diseases most affected the strawberry crop in the experimental plot were Phytophthora fragariae and Fusarium sp. The three products (Caldo Rizósfera, MM and M6) obtained a similar level of control than Benomyl® and Ceraquint® against Phytophthora fragariae and Fusarium sp. and superior to the bio-prepared Trichoderma, standing out Caldo Rizósfera for Phytophthora fragariae and MM for Fusarium sp. Surveys looking for native Trichoderma strains should be carried out